Contractile Effects of Semaglutide in the Human Atrium - Joachim Neumann; Katarína Hadová; Jan Klimas; Britt Hofmann; Ulrich Gergs (MDPI AG, 2024)
Semaglutide is a glucagon-like peptide 1 receptor (GLP-1R) agonist. GLP-1R agonists are used to treat type 2 diabetes and obesity. It is currently unknown whether semaglutide can directly increase force of contraction (FOC) in the human heart. We tested the hypothesis that semaglutide might increase the FOC in the isolated human atrium. To this end, we conducted contraction experiments in isolated human right atrial muscle preparations (HAP). HAP were obtained during open-heart surgery. We detected a concentration- and time-dependent positive inotropic effect (PIE) of semaglutide in HAP. These PIEs were accompanied by increases in the rates of tension development and tension relaxation and a reduction in muscle relaxation time. The PIE of semaglutide in HAP was attenuated by H89, an inhibitor of the cyclic AMP-dependent protein kinase and by ryanodine, an inhibitor of sarcoplasmic Ca2+ release. Semaglutide up to 100 nM failed to exert a PIE in isolated electrically paced (1 Hz) wild-type mouse left atrial preparations studied for comparison. Our data suggest that semaglutide can increase the FOC in the atria of patients at therapeutic drug concentrations.